Effectiveness and Validation of the Italian Translation of the Low Anterior Resection Syndrome Score in an Italian High-Volume University Hospital - De Simone, Veronica; Litta, Francesco; Persiani, Roberto; Rizzo, Gianluca; Sofo, Luigi; Menghi, Roberta; Santullo, Francesco; Biondi, Alberto; Coco, Claudio; Sacchetti, Franco; Longo, Fabio; Attalla El Halabieh, Miriam; et al. (Frontiers in Surgery, 2022)
Background. The low anterior resection syndrome (LARS) score is a validated questionnaire developed in Denmark to measure the severity of bowel dysfunction after low anterior resection. This retrospective study aimed to assess the effectiveness of the LARS score in the Italian language in a population of Italian patients who underwent low anterior resection for rectal cancer. The convergent and discriminative validity and the test-retest reliability of the score were investigated. Methods. A cohort of two hundred and five patients treated with low anterior resection were enrolled in an Italian high-volume university hospital between January 2000 and April 2018. The Italian version of the LARS score (tested twice), as translated from English original version, a single question on quality of life and the EORTC QLQ-C30 questionnaire were submitted to patients. Results. A high proportion of patients showed a perfect or moderate fit between the LARS score and QoL categories (convergent validity, p<0.0005). All differences regarding the items of the EORTC QLQ-C30 functional scales were statistically significant (p<0.0005). The LARS score was able to discriminate between groups of patients who received or did not receive preoperative chemoradiotherapy (p<0.0005) and those who received total or partial mesorectal excision (p<0.0005). The test-retest reliability was excellent (intraclass correlation coefficient 0.96). Conclusion. The Italian translation of the LARS score is an easy and reliable tool for assessing bowel dysfunction after low anterior resection and its routine use in clinical practice should be recommended.